Modifikasi Matras Lantai Dalam Pembelajaran Senam Lantai Materi Roll Depan Dan Roll Belakang Bagi Siswa Sma Negeri 3 Semarang Tahun 2022 (Indonesian Journal for Physical Education and Sport, 2022)
Facts on the ground show that at SMA Negeri 3 Semarang, the learning activities of floor gymnastics for the front roll and back roll materials are not much in demand by students. The cause of the low interest of students is because they feel ashamed and afraid, think it is too difficult to do it, and cannot balance the body. It is dominated by female students and students who have fat bodies. From the facts in the field, the researchers created a tilted mattress tool to help students perform front roll and back roll motion skills. This research is a development research, which uses the Research and Development method. The product development procedures are: (1) information gathering, (2) initial planning, (3) developing the initial product, (4) expert validation, (5) initial revision, (6) small-scale test (50 students), (7 ) product revision, (8) large scale test (80 students), (9) final product revision, (10) final results. This research produces a product, namely a tilting mattress tool. Data was collected using questionnaires obtained from expert evaluations and student questionnaires. Based on the results of the development, small-scale trials obtained a percentage of 79.34% (Good), the results of large-scale trials were 78.22% (Good), and for expert validation tests obtained a percentage of 86.66% (Good). The conclusion of this study is based on the assessment criteria that have been determined, the product of this tilting mattress aid is included in the good criteria for use. Suggestions for schools, teachers, and students can participate and contribute in the use of modified floor mats in learning floor exercise with front roll and back roll materials.